2019
DOI: 10.1371/journal.pone.0224422
|View full text |Cite
|
Sign up to set email alerts
|

Are census data accurate for estimating coverage of a lymphatic filariasis MDA campaign? Results of a survey in Sierra Leone

Abstract: BackgroundPreventive chemotherapy was administered to 3.2 million Sierra Leoneans in 13 health districts for lymphatic filariasis, onchocerciasis, and soil transmitted helminthes from October 2008 to February 2009. This paper aims to report the findings of a coverage survey conducted in 2009, compare the coverage survey findings with two reported rates for lymphatic filariasis coverage obtained using pre-mass drug administration (MDA) registration and national census projections, and use the comparison to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Absenteeism could be attributed to migration due to occupation where people move to other localities for farming activities, casual labor or to urban areas for employment. Migration of persons negatively affects MDA uptake and the findings are consistent with those of a study conducted in Sierra Leone [25]. Other reasons contributing to absenteeism could be lack of awareness of distribution mode and schedules for MDA due to inadequate community sensitization activities that lack repeated messaging and reminders.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Absenteeism could be attributed to migration due to occupation where people move to other localities for farming activities, casual labor or to urban areas for employment. Migration of persons negatively affects MDA uptake and the findings are consistent with those of a study conducted in Sierra Leone [25]. Other reasons contributing to absenteeism could be lack of awareness of distribution mode and schedules for MDA due to inadequate community sensitization activities that lack repeated messaging and reminders.…”
Section: Discussionsupporting
confidence: 82%
“…The study by Krentel et al, (2017), explains how health systems' challenges such as when supplies are inadequate for the program activities affect implementation of the program by becoming challenges of the CDDs [28]. Kamara et al, (2019) recommend pre-MDA registrations in areas where populations are highly mobile which are implemented correctly to avoid missing pockets of population as a way of ensuring that CDDs receive adequate supply of drugs for distributions [25]. The Kenyan NTD program is encouraged to collaborate with all relevant stakeholders to ensure that no households miss out on registration and subsequent drug distribution for successful LF campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…13 For example, in Sierra Leone, a study found populations in two districts to be higher than projected from census data following post-conflict population growth due to reopening of mines resulting in post-war employment opportunities. 39 If there are concerns about denominator accuracy, the population data can be triangulated using other data sources, such as health facility catchment area populations, community drug distributor pre-MDA registration, and remote sensing data using nightlights and land use. 21 39 Furthermore, the quality of reported data can be reviewed during supportive supervision visits and data quality assessments to determine which aspects of the reporting system are not functioning well, and to identify actions to strengthen the system such as improved training on data collection, increased supervision or revising data collection tools.…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, and elsewhere, lymphatic filariasis MDA activities are already burdened with barriers to attaining optimal treatment coverage [ 26 29 ], facilitated by inaccurate reported data [ 30 32 ] and socio-cultural and health system challenges [ 33 ]. As such, more effort will be required to address the MDA challenges during the COVID-19 era.…”
Section: Discussionmentioning
confidence: 99%